From Pipe Cleaners and Pony Beads to Apps and 3D Glasses: Teaching Protein Structure - Pamela A. Marshall (American Society for Microbiology, 2014)

(untitled)
Students often self-identify as visual learners and prefer to engage with a topic in an active, hands-on way. Indeed, much research has shown that students who actively engage with the material and are engrossed in the topics retain concepts better than students who are passive receivers of information. However, much of learning life science concepts is still driven by books and static pictures. One concept students have a hard time grasping is how a linear chain of amino acids folds to becomes a 3D protein structure. Adding three dimensional activities to the topic of protein structure and function should allow for a deeper understanding of the primary, secondary, tertiary, and quaternary structure of proteins and how proteins function in a cell. Here, I review protein folding activities and describe using Apps and 3D visualization to enhance student understanding of protein structure.